High-Throughput Testing of Urogenital and Extragenital Specimens for Detection of Chlamydia Trachomatis and Neisseria Gonorrhoeae with Cobas(®) CT/NG - Marlowe, Elizabeth M. (Eur J Microbiol Immunol (Bp), 2017)
We compared the analytical and clinical performance of cobas(®) CT/NG for use on the Cobas(®) 6800/8800 Systems with the Cobas(®) 4800 CT/NG Test from urogenital and extragenital specimens in over 12,000 specimens from both male and female subjects in Germany and the United States. The analytical sensitivity was ≤40 EB/ml for Chlamydia trachomatis (CT) and ≤1 CFU/ml for Neisseria gonorrhoeae (NG). Using clinical specimens, the overall percent agreement with the Cobas(®) 4800 CT/NG Test was >98.5%. Across urogenital specimens, there were 93 discrepant specimens; 76 (93.8%) of 81 CT discrepant specimens were 6800+/4800– and 10 (83.3%) of 12 NG discrepant specimens were 6800+/4800–. Sequencing verified CT results for 45 (61.6%) of 73 samples positive by 6800 and 1 (20%) of 5 positive by 4800. Similarly, 7 (70.0%) of 10 NG samples positive by 6800 and 1 of 2 positive by 4800 were confirmed by sequencing. Among discrepant extragenital specimens (all 6800+/4800–), 7 (50%) of 14 oropharyngeal and 23 (76.7%) of 30 anorectal CT discordant samples were confirmed as CT positive by sequencing; all 8 anorectal and 20 (90.9%) of 22 oropharyngeal NG discordant results were also confirmed as NG positive. In conclusion, Cobas(®) CT/NG for use on the Cobas(®) 6800/8800 Systems provides high-throughput automated solutions for sexually transmitted infection (STI) screening programs.